Isometric balance of forces of separate muscle groups of persons with visual impairments depending on physical activity - Mockevičienė, Daiva; Savenkovienė, Agnė (Social Welfare: Interdisciplinary Approach, 2012)
The aim of the research is to define and assess the isometric balance of forces of separate muscle groups of persons with visual impairments and its dependence on physical activity. In the research 38 respondents participated voluntarily: the respondents having moderate degree of acquired visual impairment (severe eye weakness) (n = 15) and the respondents without visual impairments (n = 23). The age of the respondents was 18 - 69 years. The research was performed in 2010-2011. The methods of the research: testing with the diagnostic equipment “Back – Check”, by which the isometric balance of forces of separate muscle groups (flexors/extensors, lateral (left/right)) has been evaluated and survey using International Physical Activity Questionnaire, by which the level of the respondents’ physical activity has been measured. The results of testing have been processed, assessed and compared with referential data with Dr. Wolff “Back – Check” software. The results have been analyzed according to individual parameters of every respondent: age, gender, weight, height. Having performed the research it has become clear that the differences in evaluations of the isometric balance between different research groups and separate muscle groups and of the isometric balance of forces and different levels of physical activity of persons with visual impairments are not statistically significant.